Therapeutic potential of Simvastatin in ALS: Enhanced axonal integrity and motor neuron survival through Apoa4 and Alb modulation - Song Luo; Xiaorui Wang; Bo Ma; Dongliang Liu; Li Li; Lijin Wang; Ning Ding; Liangyu Zou; Jie Wang; Jialin Pan; Daoqian Sang; Huadong Zhou; et al. (Biomolecules & Biomedicine)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by the selective death of motor neurons in the spinal cord, brainstem, and motor cortex. This study investigates the effects of simvastatin on the G93A-copper/zinc superoxide dismutase (G93ASOD1) transgenic mouse model of ALS. The experiment included three groups: C57BL/6 wild-type (WT) mice, C57BL/6J SOD1G93A mice treated with PBS (SOD1G93A + PBS), and C57BL/6J SOD1G93A mice treated with simvastatin (SOD1G93A + simvastatin). The primary endpoints were survival rates, body weight changes, performance in pole climbing and suspension tests, and neurological deficit scores. Pathological changes were assessed using H&E staining, transmission electron microscopy, Nissl staining, and Masson staining. Proteomic and metabolomic analyses were performed to identify differentially expressed proteins (DEPs) and metabolites. Quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting were used to measure gene expression. Although there were no significant differences in survival rates, body weight, pole climbing, and suspension test performance, or neurological deficit scores between the SOD1G93A + simvastatin and SOD1G93A + PBS groups, simvastatin treatment improved axonal organization within the spinal cord, increased the number of neurons, and reduced cytoplasmic swelling and gastrocnemius fibrosis. A total of 47 DEPs and 13 differential metabolites were identified between the SOD1G93A + PBS and SOD1G93A + simvastatin groups. Notably, the expression levels of Apoa4 and Alb were elevated in the SOD1G93A + simvastatin group compared to the SOD1G93A + PBS group. Our results suggest that simvastatin may have potential therapeutic effects in ALS, likely involving the modulation of Apoa4 and Alb expression.